Cognitive Behavioral Therapy in the Treatment of Insomnia. Issue 2 (February 2018) - Haynes, James; Talbert, Malissa; Fox, Steven; Close, Elizabeth
Abstract : Abstract: Insomnia disorder is present in as much as 30% of the general adult population. Given the significant adverse effects of pharmacotherapy, cognitive behavioral therapy (CBT) has been found to be an effective alternative in individuals with insomnia. CBT for insomnia (CBTi) encompasses sleep hygiene, stimulus control, sleep restriction, cognitive therapy, and relaxation training. In this article we review evidence that establishes CBTi as a useful treatment affecting remission, sleep onset latency, wakefulness after sleep, sleep efficiency, and sleep quality in adults with insomnia to include older adults and adolescents. In addition, we briefly highlight various CBTi delivery methods as well as barriers to accessing this safe and effective therapy. Abstract : Cognitive behavioral therapy for insomnia (CBTi) has proved to be an effective stand-alone and adjunctive therapy for insomnia in numerous age groups. Increasing efforts to find nonpharmacologic alternatives to combat the sequelae of insomnia have led in the last 10 years to research testing the effectiveness of CBTi in primary and secondary insomnia. This article provides a brief overview of the data supporting the use of CBTi for insomnia disorders in general and within specialized age groups.